2021
DOI: 10.1021/acsmaterialslett.1c00628
|View full text |Cite
|
Sign up to set email alerts
|

An Electrically Conductive Tetrathiafulvalene-Based Hydrogen-Bonded Organic Framework

Abstract: Recent advancements in the development of conductive metal− organic frameworks (MOFs) and covalent organic frameworks (COFs) have sparked interest in a variety of applications that leverage electronic materials due to the inherent tunability, porosity, and crystallinity associated with these materials. Hydrogen-bonded organic frameworks (HOFs) comprise an emerging class of complementary porous materials that assemble crystalline networks mainly from intermolecular hydrogen-bonding interactions; however, relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 67 publications
0
41
0
Order By: Relevance
“…Through the rational design of organic building blocks with geometric symmetry, planar molecules with diverse π-conjugated systems can coordinate to each other through intermolecular H-bonding interactions to form a single layer, and multiple layers pack together through strong π–π-stacking interactions to form a 3D framework with one-dimensional (1D) channels throughout the structure. HOFs that contain large, π-conjugated aromatic molecules as building blocks exhibit significantly enhanced thermal stabilities and increased chemical resistance to organic solvents and acidic or basic aqueous solutions due to the inert reactivity of the tectons (Figure ) (see refs , , , , , , , , , , , , , , , , , , , , , , , ). Several groups have independently demonstrated that HOFs with shape-fitted π–π-stacking interactions not only show type III stability upon desolvation but also become even more stable as the effective π–π-stacking areas become larger (Table ).…”
Section: Design Rules Of Stable Hofsmentioning
confidence: 99%
“…Through the rational design of organic building blocks with geometric symmetry, planar molecules with diverse π-conjugated systems can coordinate to each other through intermolecular H-bonding interactions to form a single layer, and multiple layers pack together through strong π–π-stacking interactions to form a 3D framework with one-dimensional (1D) channels throughout the structure. HOFs that contain large, π-conjugated aromatic molecules as building blocks exhibit significantly enhanced thermal stabilities and increased chemical resistance to organic solvents and acidic or basic aqueous solutions due to the inert reactivity of the tectons (Figure ) (see refs , , , , , , , , , , , , , , , , , , , , , , , ). Several groups have independently demonstrated that HOFs with shape-fitted π–π-stacking interactions not only show type III stability upon desolvation but also become even more stable as the effective π–π-stacking areas become larger (Table ).…”
Section: Design Rules Of Stable Hofsmentioning
confidence: 99%
“…Transport measurements for MUV-20a , MUV-20b , and MUV-21 were performed using two-contact probe pressed-pellet devices measured at room temperature (300 K) (Figure S46), revealing conductivity values of 6.07 × 10 –7 , 1.35 × 10 –6 , and 6.23 × 10 –9 S cm –1 , respectively (see Table S11). This indicates that MUV-20a and MUV-20b behave as semiconductors, presenting electrical conductivities similar to those reported for Cd 2 (TTFTB) and TTF-COF after being oxidized with iodine and more than 10 times higher than iodine-doped HOF-110 (see Table S12 for comparative values with all reported MOFs and HOFs containing the TTFTB unit). In contrast, non-zwitterionic MUV-21 behaves as an insulator due to the absence of charge carriers.…”
Section: Results and Discussionmentioning
confidence: 99%
“…41 A very recent development in TTFbased HOFs has been shown by Farha and co-workers, who have prepared a HOF with a naphthalene derivative of TTF, which, upon oxidation with I 2 , becomes a semiconductor (conductivity of 6.0 × 10 −7 S cm −1 ). 42 Herein, we present the use of the H 4 TTFTB molecule to prepare two new porous HOFs, in which the building block ligand has a zwitterionic character. These materials, denoted MUV-20a and MUV-20b, do not require additional doping for electrical charge transport, resulting in two porous conducting HOFs while preserving their crystalline porosity.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 20 Farha and co-workers reported post-synthetic incorporation of iodine within conductive HOF-110 affording a 30-fold improvement in electrical conductivity. 35 Sun and Luo et al proposed to load the doxorubicin onto the surface of a porphyrin-based HOF, which provided synergistic chemotherapy–photodynamic therapy–photothermal therapy effects. 36 These works inspire us to construct functionalized HOFs for the application of white light-emitting diodes (WLEDs) which is difficult to be achieved by a HOF material itself.…”
Section: Introductionmentioning
confidence: 99%